Thrombophilia in Pregnancy - Hotoleanu, Cristina (International Journal of Cardiovascular Practice, 2019)
Pregnancy represents a physiologic hypercoagulable state. The presence of inherited thrombophilias (factor V Leiden, prothrombin G20210A mutation, deficiencies of protein C, protein S and antithrombin) or acquired thrombophilias (antiphospholipid syndrome) increases the risk for venous thromboembolism, which represents one of the most common causes of direct maternal death. The clinical diagnosis of thrombosis can be difficult because of the overlap of symptoms with pregnancy-related manifestations. Antiphospholipid syndrome is correlated with early and late pregnancy complications whereas the association between the inherited thrombophilias and adverse pregnancy outcomes is still controversial. The psychological impact of thrombophilia in pregnancy should be also taken into consideration to prevent the negative effects of anxiety and stress on mother’s health and on birth outcomes. Thrombophilia testing in pregnancy is recommended only in cases in which the result is likely to influence the therapeutic decision. Low-molecular-weight heparins are the preferred anticoagulant for prophylaxis and therapy of thromboembolic events in pregnancy, presenting a low incidence of side effects. Future research is required to establish the optimal therapeutic strategy in pregnant women with thrombophilia, based upon a better stratification, in order to prevent thromboembolism and to improve pregnancy outcomes.